Source Indication and Geochemical Significance of Sedimentary Organic Matters from the Xisha Area, the South China Sea - Yan Li (MDPI AG, 2021)
Although various geochemical and geophysical investigations have already indicated a great resource potential in the Xisha area of the South China Sea, the origin of organic matter and molecular evidence for tracing the migration of hydrocarbons from deep petroleum reservoirs are still lacking. In this study, systematic organic geochemical analyses, including bulk organic matter parameters and lipid biomarkers were performed for deep sediments from two cores. The C/N ratios and δ13C and δ15N values of organic matter in most of the samples, together with the maxima of short-chain n-alkanoic acids and mid-chain n-alkanols, high abundances of monounsaturated fatty acids C18:1ω9 and C22:1ω13, jointly indicate the dominance of marine organic matter. n-Alkanes in sediments from core GMGS4-XH-W06B are characterized by small unresolved complex mixture (UCMs) humps, high odd/even predominance (OEP) and carbon preference index (CPI) values, clearly exhibiting characteristics of modern sediments. However, the sediments for core GMGS4-XH-W03B are featured with big UCMs, associated with OEP and CPI values around 1.0, showing signatures of petroleum hydrocarbons from high maturity sources. Considering the geologic background, the biomarker signatures are solid evidence for indicating the existence of underlying petroleum reservoirs, and may provide the valuable information for assessing the hydrocarbon resources in the Xisha area.